Clinical Features of Crohn’s Disease Stratified by Age at Diagnosis According to Montreal Classification - Xiang J; Li J; Liu C; Tian S; Dong W (Dove Medical Press, 2023)
Jiankang Xiang,1 Jiao Li,1 Chuan Liu,1 Shan Tian,2 Weiguo Dong1 1Department of Gastroenterology, Renmin Hospital of Wuhan University, Wuhan, 430060, People's Republic of China; 2Department of Infectious Diseases, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People's Republic of ChinaCorrespondence: Weiguo Dong, Email dongweiguo@whu.edu.cnAim: The differences of clinical characteristics stratified by age at diagnosis especially according to Montreal classification were rarely studied in China. This study aimed to evaluate and compare the clinical features in various groups of CD patients stratified by age at diagnosis.Methods: A cross-sectional study of CD patients was conducted through a stratified sampling according to Montreal classification. Patients were divided into three groups by age at diagnosis: group A1 (< 17 years old), group A2 (17 to 40 years old), and group A3 (> 40 years old). The clinical characteristics, laboratory tests, radiographic, and endoscopic features were analyzed by statistics.Results: We enrolled 259 CD patients for the study. There was male predominance under 40 years old. Compared to group A1, more female patients were presented in group A3. There were more patients had perianal fistulas in group A1 compared to group A2 and group A3. Compared with group A1, patients in group A2 were associated with lower total protein (TP) levels. The mean TP and platelet count (PC) levels in group A3 were lower than group A1. Patients in group A1 had a lower rate of stricturing (B2) disease behavior than group A2 and group A3, and patients in group A3 who had a B2 disease behavior were higher than group A2. Those differences could guide early treatment or inventions for CD patients who might progress to a more complex disease behavior.Conclusion: CD patients stratified by age at diagnosis according to Montreal classification had different clinical symptoms, laboratory test results as well as disease locations and behaviors.Keywords: Crohn's disease, age at diagnosis, Montreal classification, clinical characteristics